A critical look into effects of electrode pore morphology in solid oxide fuel cells. Issue 6 (14th November 2016) - Niu, Yinghua; Lv, Weiqiang; Rao, Gaofeng; He, Weidong; He, Jiarui
Abstract : Knudsen diffusion, an important form of gas transport in sub‐micro/nanoscale porous electrodes of solid oxide fuel cells (SOFCs), is evaluated typically based on the assumption of isotropic cross‐sections of electrode pores. As a consequence, errors are induced in the evaluation of gas transport and polarization loss of SOFCs with irregular, anisotropic pore morphology. Here, a numerical model is derived to investigate the impact of pore morphology on Knudsen diffusivity and effective total diffusivity in porous SOFC electrodes. Based on the model, the correlation between pore morphology and important parameters of SOFCs, including limiting current density (LCD) and concentration polarization (CP), is evaluated. As the aspect ratio of pore cross‐section increases, the gas diffusivity in SOFC electrodes decreases, and then nontrivial variations in LCD and CP are induced. This work facilitates the accurate evaluation of gas transport in SOFCs as well as the rational design of electrode microstructure of SOFCs. © 2016 American Institute of Chemical Engineers AIChE J, 63: 2312–2317, 2017